CRITICAL DISCOURSE ANALYSIS OF MARITIME VALUES IN THE DJUANDA DECLARATION MATERIAL: ANALISIS WACANA KRITIS NILAI-NILAI MARITIM PADA MATERI DEKLARASI DJUANDA - Siska Amelia; Leli Yulifar (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This articel aims to describe critical discourse analysis of the Djuanda Declaration material in the 2013 revised 2018 Indonesian History book through a qualitative descriptive approach. This approach uses Teun A. Van Dijk's critical discourse analysis model which includes three dimensions, namely dimension 1) text (macrostructure, superstructure and microstructure); 2) social cognition; and 3) social context. The results of this research show that the material text of the Djuanda Declaration, which is published in the 2018 revised 2018 History of Indonesia book, provides information about efforts to protect Indonesia's territorial sea boundaries and the benefits for Indonesia, namely being able to unite Indonesia's territories and the natural resources of the sea can be utilized optimally.